Variability and Costs of Low-Value Preoperative Testing for Cataract Surgery Within the Veterans Health Administration - Mudumbai, Seshadri C. (JAMA Netw Open, 2021)
IMPORTANCE: The Choosing Wisely guidelines indicate that preoperative testing is often unnecessary and wasteful for patients undergoing cataract operations. However, little is known about the impact of these widely disseminated guidelines within the US Veterans Health Administration (VHA) system. OBJECTIVE: To examine the extent, variability, associated factors, and costs of low-value tests (LVTs) prior to cataract operations in the VHA. DESIGN, SETTING, AND PARTICIPANTS: This cohort study examined records of all patients receiving cataract operations within the VHA in fiscal year 2017 (October 1, 2016, to September 31, 2017). Records from 135 facilities nationwide supporting both ambulatory and inpatient surgery were included. EXPOSURES: A laboratory test occurring within 30 days prior to cataract surgery and within 30 days after clinic evaluation. MAIN OUTCOMES AND MEASURES: Overall national and facility-level rates and associated costs of receiving any of 8 common LVTs in the 30 days prior to cataract surgery. The patient characteristics, procedure type, and facility-level factors associated with receiving at least 1 test, the number of tests received, and receipt of a bundle of 4 tests (complete blood count, basic metabolic profile, chest radiograph, and electrocardiogram). RESULTS: A total of 69 070 cataract procedures were identified among 50 106 patients (66 282 [96.0%] men; mean [SD] age, 71.7 [8.1] years; 53 837 [77.9%] White, 10 292 [14.9%] Black). Most of the patient population had either overweight (23 292 [33.7%] patients) or obesity (27 799 [40.2%] patients). Approximately 49% of surgical procedures (33 424 procedures) were preceded by 1 or more LVT with an overall LVT cost of $2 597 623. Among patients receiving LVTs, electrocardiography (7434 patients [29.9%]) was the most common, with some patients also receiving more costly tests, including chest radiographs (489 patients [8.2%]) and pulmonary function tests (127 patients [3.4%]). For receipt of any LVT, the intraclass correlation coefficient was 0.61 (P < .001) at the facility level and 0.06 (P < .001) at the surgeon level, indicating the substantial contribution of the facility to amount of tests given. CONCLUSIONS AND RELEVANCE: Despite existing guidelines, use of LVTs prior to cataract surgery is both common and costly within a large, national integrated health care system. Our results suggest that publishing evidence-based guidelines alone—such as the Choosing Wisely campaign—may not sufficiently influence individual physician behavior, and that system-level efforts to directly deimplement LVTs may therefore necessary to effect sustained change.